Optimization of synthesis conditions for (1-X) Bi (Mg3/4W1/4) O3-XPbTiO3 piezoceramics - Verma N.K.; Singh A.K. (My University, 2025)
Synthesizing the Bi-based perovskite ferroelectric samples is mostly difficult due to formation of impurity phases. In the present work, we have optimized the synthesis conditions for (1-x)Bi(Mg3/4W1/4)O3-xPbTiO3 piezoceramics which is an important solid solution with the morphotropic phase boundary. The ball milled powders were calcined at various temperatures namely 500 oC, 600 oC, 700 oC, 750 oC, 800 oC and 850 oC in a muffle furnace for 6 hrs to optimize the calcination temperature. The optimum calcination temperature is 850 oC for 6 hours duration while the optimum sintering temperature is 990oC for 3hrs. The SEM characterization of the sintered sample reveals dense microstructure with average grain size ~2µm. © 2019 American Institute of Physics Inc.. All rights reserved.